The syllabification of /sw/ in Italian and the phonological status of /w - Piero Cossu (Isogloss)
This study investigates the phonetics and phonology of word-initial /sw/ clusters in Italian, aiming to discern the syllabic parsing of the sequence and the phonological status of the glide /w/. Previous studies have reported a dual status of /w/ in Italian, consonantal in loanwords versus vocalic in native lexemes, apparently dependent on the graphemic form of /w/, i.e. ⟨w⟩ and ⟨u⟩. The /s/-voicing pattern before the glide was used as a diagnostic to determine the glide’s status: a consonantal glide should trigger /s/-voicing, like any other voiced consonant in Italian. Differently, vocalic glides should pattern like vowels in being unable to trigger the voicing of /s/. Two hypotheses are presented: the Loanword Phonology Hypothesis (LPH), which predicts /w/ to systematically behave as a consonant in loanwords, while the Orthographic Hypothesis (OH) predicts so only when the glide is written ⟨w⟩. The analysis was based on acoustic data originally collected, focusing on the outputs of /s/. Results show that OH better accounts for the pattern observed than LPH. Phonological implications of this finding are discussed.